Biotechnology project-based learning encourages learning and mathematics application - Jiménez-Gaona, Yuliana; Vivanco-Galván, Oscar (Frontiers in Education, 2024)
Project-based learning (PBL) is a promising approach to enhance mathematics learning concepts in higher education. Here, teachers provide guidance and support to PBL implementation. The objective of this study was to develop PBL-based biotechnological projects as a strategy for mathematics learning. The methodology design was applied to 111 university students from Biochemical, Chemical Engineering and Business Administration careers. Knowledge, skills, perceptions, and engagement were measured through questionnaires, workshops, rubrics, and survey instruments. As a result, the paired comparison between tests, questionnaires and project shows significant differences (P<.001) between the experimental group and the control group. It is concluded that the teaching of mathematics should be oriented to the development of competencies, abilities, and skills that allow students to generate real solutions and broaden their vision of the applicability of their knowledge using new learning strategies. Key words: Mathematical models, Biotechnology, Project based learning.Science, technology, engineering, and mathematics (STEM) education has become a crucial topic both inside and outside of school (Han et al., 2015). Currently, mathematics learning tends to be oriented towards textbooks, and students can only work on math problems based on what the teacher exemplifies; however, if given different contextbased problems, they will have difficulty solving them (Fisher et al., 2020). Likewise, the traditional classroom model does not encourage student's interest in STEM (Sahin, 2009) The research gap is between what students learn at the university and what they really need in the workplace (Holmes et al., 2015). Higher education institutions have been trying to provide students with both (i) hard skills, such as cognitive knowledge and professional skills (Vogler et al., 2018), and (ii) soft skills, such as problem-solving and teamwork (Lennox and Roos 2017). However, these skills are difficult to achieve through traditional learning. One learning that creates an active, collaborative atmosphere, and can increase selfconfidence in students is Project-based learning (PBL) (Cruz et al., 2022; Guo et al., 2022;Markula and Aksela 2022). The PBL method is applied as a teaching model that involves